'A Waste of Time'? 2nd Circuit Reconsiders Class Waivers As Mandatory Arbitration Heads to Supreme Court. Issue 9 (October 2016) - Bleemer, Russ
Abstract : The end of summer turned out to be the beginning of the final stages of a crucial four‐year‐old argument over the use of arbitration, and the future of the conflict resolution process in U.S. contracts.